2006
DOI: 10.1016/j.cell.2006.08.033
|View full text |Cite
|
Sign up to set email alerts
|

SIN1/MIP1 Maintains rictor-mTOR Complex Integrity and Regulates Akt Phosphorylation and Substrate Specificity

Abstract: Mammalian target of rapamycin (mTOR) controls cell growth and proliferation via the raptor-mTOR (TORC1) and rictor-mTOR (TORC2) protein complexes. Recent biochemical studies suggested that TORC2 is the elusive PDK2 for Akt/PKB Ser473 phosphorylation in the hydrophobic motif. Phosphorylation at Ser473, along with Thr308 of its activation loop, is deemed necessary for Akt function, although the regulatory mechanisms and physiological importance of each phosphorylation site remain to be fully understood. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

81
1,086
6
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,234 publications
(1,194 citation statements)
references
References 69 publications
81
1,086
6
5
Order By: Relevance
“…16,19,35 Little is known, however, about the physiological stimuli that regulate fission yeast TORC2, whereas insulin and growth factors activate mammalian TORC2 (mTORC2) in a PI3K-dependent manner. 7,8,[36][37][38] In this report, we show that TORC2 in fission yeast is responsive to glucose and that the functional TORC2-Gad8 pathway is essential for cell proliferation in glucose-limited environment. Our mutational analysis indicated that the glucose regulation of fission yeast TORC2 is not dependent on the cAMP pathway, a signaling mechanism known to be responsive to extracellular glucose.…”
Section: Introductionmentioning
confidence: 95%
“…16,19,35 Little is known, however, about the physiological stimuli that regulate fission yeast TORC2, whereas insulin and growth factors activate mammalian TORC2 (mTORC2) in a PI3K-dependent manner. 7,8,[36][37][38] In this report, we show that TORC2 in fission yeast is responsive to glucose and that the functional TORC2-Gad8 pathway is essential for cell proliferation in glucose-limited environment. Our mutational analysis indicated that the glucose regulation of fission yeast TORC2 is not dependent on the cAMP pathway, a signaling mechanism known to be responsive to extracellular glucose.…”
Section: Introductionmentioning
confidence: 95%
“…Among the residues that are phosphorylated over the course of Akt kinase activation is Ser473 in the C-terminal portion of the protein 40,41 . Depletion of Ofd1 or Bbs4 reproducibly results in reduced phospho-Akt (pSer473) after insulin stimulation (5 mU ml À 1 , 15 min) in MIN6m9 cells (Fig.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 99%
“…The two TOR complexes were initially identified in yeast and subsequently were also characterized in Drosophila and mammalian cells. TORC1 contains mTOR, mLST8, PRAS40, and Raptor, whereas TORC2 contains mTOR, mLST8, Rictor, and Sin1 (5)(6)(7)(8)(9)(10)(11)(12). TORC1 is responsible for phosphorylation of Thr 389 of S6K1 (ribosomal protein S6 kinase) and 4EBP1 (eukaryote initiation factor 4E-binding protein), two important regulators in protein synthesis (1).…”
mentioning
confidence: 99%